Retrospective analysis of head and neck masses diagnosed by cytology in a tertiary care centre - Dr. Subitha K; Dr. Sheeja. S; Dr. Renu Thambi; Dr. Jayalakshmy P.L; Dr. Lillykutty Pothen; Dr. Letha.V (Tropical Journal of Pathology and Microbiology, 1970)
Introduction: Fine Needle Biopsy of head and neck masses as a minimally invasive technique is particularly suitable in this sensitive area where an incisional biopsy can cause problems. A cytological diagnosis of a non-neoplastic lesion or confirming suspected metastatic or recurrent tumor can obviate the need for surgery. FNAC can effectively distinguish between benign and malignant cystic lesions of the head and neck.Aim: The aim of this study is to categorise the various head and neck lesions diagnosed by cytology and to assess the diagnostic utility of FNAC.Materials and Methods: All the cases of head and neck masses diagnosed by cytology during the period of one year were analysed. Age and sex distribution was noted. Lesions were mainly categorised into lesions of thyroid, salivary gland and lymph node. Each group were then subcategorised into various groups depending upon the neoplastic and nonneoplastic nature. In some cases histopathologic correlation was done.Results: Thyroid lesions formed 61.5 % (475) of the total number of head and neck masses. 99% of the cases were benign lesions. Lymphadenopathies formed 34 % (262) of the total number of head and neck masses. Most common diagnoses were reactive lymphadenitis (43.5%) followed by granulomatous lymphadenitis (12.5%). Salivary gland lesions formed 4.5 % (35) of the total number of head and neck masses. Sialadenitis was the most common among the benign lesions (40 %) and pleomorphic adenoma was commonest among neoplasms (37 %).Conclusion: FNAC is a reliable, safe, cost-effective and minimally invasive procedure. FNAC can be advised as a primary diagnostic tool.